Governing Religious Identity: State Policy and the Convergence of Muhammadiyah and Nahdlatul Ulama - Aris Munandar; Suryani (Balai Penelitian dan Pengembangan Agama Jakarta, 2026)
This study examines how contemporary state policies are transforming the traditions and identities of Muhammadiyah and Nahdlatul Ulama (NU), and how both organisations are responding to and negotiating these changes in public life. Drawing on Foucault’s concept of governmentality, Talal Asad’s thesis on the state’s construction of ‘religion’, and coercive isomorphism, this qualitative study—comprising interviews, observation and document analysis—examines policies such as religious moderation, the Pancasila ideology and the regulation of civil society organisations. The findings indicate that the state acts not only as a regulator but also as a normative and discursive force that limits the legitimacy of religious practices; the identities of Muhammadiyah and NU tend to converge towards the state-sanctioned discourse of ‘moderate and nationalist Islam’, although both continue to adaptively preserve their traditional characteristics. This research enriches the theory of religion-state relations by highlighting the governmental and discursive dimensions of religious regulation.